Efficiency of orthotic intervention in the rehabilitation of patients with rheumatoid arthritis - E. V. Orlova; D. E. Karateev (Современная ревматология, 2016)
Orthotic intervention is the most important element in the rehabilitation of patients with rheumatoid arthritis (RA).Objective: to evaluate the clinical efficiency of orthotic intervention in the rehabilitation of patients with RA.Patients and methods. The investigation enrolled 70 patients with RA (women, 84.3%; age, 18 to 64 years; disease duration, 3 months to 4 years) who were divided into 4 groups: 3 orthotic groups (ORLETT knee, ankle, and wrist orthoses of various fixation) and one control group (only drug therapy). The number of tender and swollen joints (TJ and SJ), pain on 100-mm VAS, erythrocyte sedimentation rate, C-reactive protein levels, DAS28, HAQ, RAPID3, and FFI scores, knee joint movement amplitudes, step test values, and hand compression force were estimated during 6 months. The clinical efficacy and comfort of orthoses and adherence to orthotic intervention were evaluated.Results. Six-month knee, ankle, and wrist orthotic intervention caused a reduction in the number of TJ and SJ, pain VAS, HAQ, RAPID3, and FFI scores, and step test values and an increase in knee flexion angle and hand compression force; at the same time, there were significant differences in those observed in the control group. The orthotic intervention failed to affect DAS28 scores and laboratory parameters. This decreased substantially (by more than 50%) the patients' needs for nonsteroidal anti-inflammatory drugs. Both a physician and a patient appreciated the comfort and clinical efficacy of orthoses greatly and adherence to their use well (86.7 to 93.3%).Conclusion. The 6-month application of knee, ankle, and wrist orthoses reduces pain syndrome and joint swelling and improves locomotor indicators, functional status, and quality of life in patients with RA, which may recommend including orthotic intervention in a comprehensive rehabilitation program.